Host immunity to Plasmodium infection: Contribution of Plasmodium berghei to our understanding of T cell-related immune response to blood-stage malaria. (February 2023) - Ibraheem, Yarob; Bayarsaikhan, Ganchimeg; Inoue, Shin-Ichi
Abstract: Malaria is a life-threatening disease caused by infection with Plasmodium parasites. The goal of developing an effective malaria vaccine is yet to be reached despite decades of massive research efforts. CD4 + helper T cells, CD8 + cytotoxic T cells, and γδ T cells are associated with immune responses to both liver-stage and blood-stage Plasmodium infection. The immune responses of T cell-lineages to Plasmodium infection are associated with both protection and immunopathology. Studies with mouse model of malaria contribute to our understanding of host immune response. In this paper, we focus primarily on mouse malaria model with blood-stage Plasmodium berghei infection and review our knowledge of T cell immune responses against Plasmodium infection. Moreover, we also discuss findings of experimental human studies. Uncovering the precise mechanisms of T cell-mediated immunity to Plasmodium infection can be accomplished through further investigations using mouse models of malaria with rodent Plasmodium parasites. Those findings would be invaluable to advance the efforts for development of an effective malaria vaccine.